Multimodal Discourse Analysis on Representation of Black Hero in Malcolm Spellman the Falcon and the Winter Soldier Series (2021) - Azizah, Anna Wafiq; Irawan, Andi Muhammad (Universitas Negeri Padang, 2023)
Multimodal discourse analysis is an interdisciplinary approach that studies how different modes of communication work together to create meaning in social interactions. The author analyzes verbal and visual elements in The Falcon and the Winter Soldier in this study. This research used the descriptive qualitative method. The aim of this study is to determine the verbal and visual elements that represent black people and to find out the relationship between verbal and visual elements in this movie. To achieve these objectives, the researcher applied the theoretical framework from Halliday & Matthiessen (2014) on the language of metafunctions, Kress & van Leeuwen (2006) on visual grammar analysis, and the analysis of inter-mode relations from Leeuwen (2005) to obtain a detailed description of the relationship between verbal and visual elements. The results of the study show that in verbal language, the ideational metafunction is dominated by the material process. Interpersonal metafunction is dominated by statement speech acts which show that the text is mostly in the form of a declarative mood. The textual metafunction contains topical unmarked and multiple themes in this movie. In the visual image, ideational metafunction is realized mostly through the reactional process. Interactive metafunction is realized through the offer gaze and the medium shot. The medium size dominates the compositional metafunction. Visual and verbal elements have elaboration and extension relations. Through the elaboration of visual grammar analysis, some visuals are used to make the verbal elements more specific, and others are used to add information not included in the verbal elements. The verbal and visual modes clarify each other's meanings and display connected and not contradictory concepts so the audience can easily understand.